ASSESSING THE DETERMINANTS OF PRIVATE WASTE COLLECTORS’ OPERATIONAL EFFICIENCY AND ITS EFFECT ON REVENUE: A CASE STUDY OF LAGOS WASTE MANAGEMENT SECTOR - Shehu Usman Adam (Malete Journal of Accounting and Finance)
Private waste collection firms play vital role in the realization of waste-related environmental goals of achieving clean environment and reduced solid waste pollution. However, little is known on such firms’ efficiency and its effect on firms’ revenue. Empirical research on the role of such firms’ operational efficiency in boosting financial performance is sparse in waste management logistic operations literature. This study analyzes the factors determining the efficiency of such private firms and its effect on their financial performance. Using secondary data obtained from the Lagos Waste Management Authority (LAWMA) for 260 Private Sector Participants (PSPs), Structural Equation Modeling (SEM) procedure was adopted to analyze the theoretically justified model specified. Relying on SEM’s capacity to address endogeneity in cross-section data, the study avoided the possibility of repeating the confounding effects in previous studies, lending more reliability to estimated parameters and conclusions. The analysis reveals that trip frequency, firm capacity, and firm experience significantly influence operational efficiency. The model’s diagnostics indicate the model has high explanatory power, lending more reliability to the estimated parameters. The study concludes that operational efficiency, achievable through enhancing trip frequency, firms’ capacity, and firms’ experience are sine qua non to enhancing the revenue generation of private waste logistics firms in the waste management sector. Thus, the study recommends the government and regulatory authorities to target policies that would aid firms’ expansion, and workers’ trainings to bridge experience gaps in the industry.